2017
DOI: 10.1590/1984-0462/;2017;35;2;00008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência De Escoliose Em Escolares Do Ensino Fundamental Público

Abstract: Objective: To evaluate the prevalence of scoliosis and the risk factors in elementary school students.Methods: A cross-sectional study was carried out in 954 students in 2015. The instrument involved was a questionnaire on postural habits, socioeconomic conditions, and demographic factors. The anthropometric measurements, including height and weight, a visual inspection of the deformity of the vertebral column, the leveling of shoulders, and the Adam’s test were obtained. The sample was calculated in the expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
0
9
0
7
Order By: Relevance
“…The spine deviation angle, equal to 5º and determined by a scoliometer, is a criterion for determining the Cobb angle equal to 20º in computer analyzes [22][23][24]. In our studies, scoliosis of the II degree and higher was observed in 9.9 % of 1922 schoolchildren in Kyiv, respectively, 13.7 % of children had all types of scoliosis, which exceeded the data of modern researchers of the world [2,7,20].…”
Section: Original Researchmentioning
confidence: 50%
See 1 more Smart Citation
“…The spine deviation angle, equal to 5º and determined by a scoliometer, is a criterion for determining the Cobb angle equal to 20º in computer analyzes [22][23][24]. In our studies, scoliosis of the II degree and higher was observed in 9.9 % of 1922 schoolchildren in Kyiv, respectively, 13.7 % of children had all types of scoliosis, which exceeded the data of modern researchers of the world [2,7,20].…”
Section: Original Researchmentioning
confidence: 50%
“…In about 20 % of cases, scoliosis is secondary to another pathological process. The remaining 80 % are cases of idiopathic scoliosis [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Foram encontrados 10 artigos, conforme demonstrado no Quadro 1. Estes foram pré-selecionados de acordo com a temática dessa pesquisa, encontrados no intervalo de tempo (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020), os quais serão explicados através de análises dos dados.…”
Section: Resultados E Discussõesunclassified
“…Metodologia: Trata-se de uma revisão integrativa na qual a busca foi realizada mediante a pesquisa nas seguintes bases de dados: Biblioteca Virtual em saúde (BVS) e Medical Literature Analysis and Retrieval System Online (Pub-Med/Medline). Os critérios de inclusão utilizados foram artigos publicados nos últimos sete anos (2013)(2014)(2015)(2016)(2017)(2018)(2019), nos idiomas português e inglês, disponibilizados de forma integral e com livre acesso ao texto e que estivessem adequados ao tema proposto. Para a exclusão dos artigos, os critérios aplicados foram estudos que não estivessem de acordo com o tema proposto, artigos de revisão, artigos que estavam fora do período determinado pelos critérios de inclusão.…”
Section: Considerações Finaisunclassified
“…Segundo Ciaccia et al (2017), as mulheres demonstraram que têm menores oportunidades de apresentar hipercifose dorsal em relação aos homens. Nos dois sexos, os alunos com idades entre 8 e 12 anos apresentaram menor chance de aparecer hipercifose dorsal em afinidade aqueles com 13 a 15 anos.…”
Section: Introductionunclassified